2019
DOI: 10.14740/jh559
|View full text |Cite
|
Sign up to set email alerts
|

The Use of R-Hyper-CVAD in a Rare Case of Primary Bone Marrow Diffuse Large B-Cell Lymphoma

Abstract: Primary bone marrow lymphoma (PBML) is a rare clinical entity. Because of its rarity, there is no standard therapy defined. Prognosis in this disease is poor, and further studies for effective treatments are needed. In this report, we will discuss a patient with PBML who was treated with a hyper-fractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone alternating with methotrexate and cytarabine (hyper-CVAD) plus rituximab regimen with a favorable outcome. We believe this is the first reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…There were 51 high-grade BCL cases, and among these 77% (48/62) were DLBCL and 5% (3/62) were left unclassifiable. 1,3,5-33 Meanwhile, there were 11 cases of low-grade BCL, and 11% (7/62) were FLs. 1,34,35 According to the character of our case, we focused more on the analysis of HGBL.…”
Section: Discussionmentioning
confidence: 99%
“…There were 51 high-grade BCL cases, and among these 77% (48/62) were DLBCL and 5% (3/62) were left unclassifiable. 1,3,5-33 Meanwhile, there were 11 cases of low-grade BCL, and 11% (7/62) were FLs. 1,34,35 According to the character of our case, we focused more on the analysis of HGBL.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Reed et al demonstrated good response to rituximab, cyclophosphamide, vincristine, doxorubicin, and dexamethasone (R-Hyper-CVAD) in a young woman with PBM-DLBCL and high-risk of CNS disease. 28 PBML has been reported to have a median overall survival (OS) ranging from 8 months to 1.8 years. 3,6,7,11,29 According to the IELSG, prognosis differs by histologic subtype with a median OS <1.5 years for those with PBM-DLBCL.…”
Section: Dovepressmentioning
confidence: 99%
“…PBML is considered as a distinct subtype of DLBCL with poor prognosis 1,2 . The use of intensive induction therapies such as R‐Hyper CVAD or R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone) followed by up‐front high‐dose chemotherapy and autologous stem cell rescue has been reported based on the assumption of poor prognosis 3,4 . However, because of its rarity, the clinical features of PBML remain unclear and there is no evidence base to support a recommendation of intensive induction therapy.…”
Section: Introductionmentioning
confidence: 99%